2021
DOI: 10.1029/2021ja029756
|View full text |Cite
|
Sign up to set email alerts
|

A Time‐Dependent Two‐Dimensional Model Simulation of Lower Ionospheric Variations Under Intense SAID

Abstract: During geomagnetically disturbed intervals, a latitudinally narrow yet longitudinally elongated zone of fast westward ion drift (or equivalently strong poleward electric field) often appears in the evening to midnight sector equatorward of the auroral oval. Galperin et al., (1973) first reported such phenomena and called them polarization jets. They were subsequently termed as "subauroralion drift" (SAID) by Spiro et al., (1979). References to early observations and to subsequent clarifications of the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 96 publications
0
34
4
Order By: Relevance
“…SAID's have been investigated in both ground and space‐based observations (e.g., Anderson et al., 1991, 1993, 2001; Archer & Knudsen, 2018; Foster et al., 1994; Karlsson et al., 1998; He et al., 2014; Mishin, 2013; Puhl‐Quinn et al., 2007). Motivated by the observations, numerous models have been constructed to study the ionospheric processes (e.g., Heelis et al., 1993; Liang et al., 2021; Moffett et al., 1992, 1998) and magnetospheric processes (Nishimura, Yang, et al., 2020; Wang et al., 2021) involved with SAID. SAID shares some similar properties with, yet differ in a few key aspects from, another subauroral flow phenomenon called the “subauroral polarisation streams” (SAPS), which is usually weaker in flow magnitude and broader in latitudinal width than SAID (e.g., Foster & Burke, 2002; Mishin et al., 2017].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAID's have been investigated in both ground and space‐based observations (e.g., Anderson et al., 1991, 1993, 2001; Archer & Knudsen, 2018; Foster et al., 1994; Karlsson et al., 1998; He et al., 2014; Mishin, 2013; Puhl‐Quinn et al., 2007). Motivated by the observations, numerous models have been constructed to study the ionospheric processes (e.g., Heelis et al., 1993; Liang et al., 2021; Moffett et al., 1992, 1998) and magnetospheric processes (Nishimura, Yang, et al., 2020; Wang et al., 2021) involved with SAID. SAID shares some similar properties with, yet differ in a few key aspects from, another subauroral flow phenomenon called the “subauroral polarisation streams” (SAPS), which is usually weaker in flow magnitude and broader in latitudinal width than SAID (e.g., Foster & Burke, 2002; Mishin et al., 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liang et al. (2021) (hereafter referred to as LJ21) presented a comprehensive and dedicated study on the role of ion Pedersen transport in the dynamic variations of the lower ionosphere in a SAID channel. Using a two‐dimensional (2D) time‐dependent model tailored to SAID conditions, LJ21 found that the transport effect of ion Pedersen drifts leads to strong density depletion and conductance drop in the lower ionosphere over a large portion of SAID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related modeling indicating the coexistence of strong conductance gradients with the strong flows of sub auroral ionization drift, is shown recently in Liang et al. (2021). The resulting conductance structuring can be a source for field‐aligned currents; these ionospherically sourced field‐aligned currents can then be unstable to tearing modes and locally accelerate ambient thermal electrons, leading to the picket fence similarity to rayed auroral curtains.…”
Section: Introduction: Background and Premisementioning
confidence: 55%
“…The model includes self‐consistent electron energy descriptions, but does not include the kinetic turbulence effects discussed in Liang et al. (2021). However, our primary focus here is the Pedersen drift from multiple flow shears, which tends to dominate in these strong channels.…”
Section: Method: Gemini Model and Example Observational Driversmentioning
confidence: 99%